Investigating the effects of elevated temperature on salinity tolerance traits in grapevine rootstocks using high‐throughput phenotyping. (22nd February 2022) - Dunlevy, J.D.; Blackmore, D.H.; Betts, A.; Jewell, N.; Brien, C.; Berger, B.; Walker, R.R.; Edwards, E. J.; Walker, A.R.
Abstract: Background and Aims: Predicted impacts of climate change—increased temperature, decreased rainfall, and reduced water availability—are expected to increase irrigation‐related salinity in Australia's major wine regions. Breeding of new abiotic stress‐tolerant rootstocks will help to mitigate these effects on viticulture. Here, we investigated the impact of elevated temperature on key salt tolerance traits of two contrasting rootstocks and a population of experimental rootstock hybrids. Methods and Results: A high‐throughput facility was used to phenotype the rootstocks, K51‐40, 140 Ruggeri and 68 K51‐40 derived hybrids, all ungrafted, under factorial salinity and temperature treatments. Elevated temperature led to increased chloride concentration in the mature laminae of most genotypes, likely driven by increased transpiration, with large differences between genotypes in the extent of the temperature response. Genetic differences were also observed for the influence of temperature on laminae sodium accumulation. Growth rate response to salinity was variable between genotypes and was independent of laminae chloride and sodium accumulation. Conclusions: High‐throughput phenomics provides a promising tool to simultaneously assess new rootstock selections for ion exclusion and growth rate response under abiotic stresses. Significance of the Study: Understanding the effect of temperature on salinity tolerance traits, and the development of novel screening tools, will help breed new rootstocks better suited to a hotter and drier future climate.